Bioprospecting of fungal entomo- and myco-pathogens - Pathan, E. K.; Patil, A. V.; Deshpande, M. V. (Advancing Frontiers in Mycology & Mycotechnology, 2019)
The pest and pathogen control in the field using fungi and their metabolites has indeed gone beyond ‘proof of concept’. However, in view of the performances of these biocontrol fungi in the fields, moreover, acceptability by the end users regarding cost-effectiveness, shelf life, intellectual property rights (IPR), the additional roles, and possible applications are being explored. Dual pathogenicity, viz. entomopathogenesis and mycoparasitism, has added the advantage of wide-spectrum biocontrol in single-crop system. In addition to plant protection, these fungi can promote plant growth. Further, in integrated pest management, the bioremediation of pesticide residues, if any, can also be achieved by these organisms. For value addition, use of cuticle-degrading and mycolytic enzymes produced as killing components can be explored in food, detergent, organic synthesis, and pharmaceutical industries. While exploring the additional applications, the safety to beneficial insects and fungi, biodiversity, and humans, in general, is also addressed.